(untitled) (The Pakistan Development Review, 1989)
The issue of the effects of growth on inequality and poverty is an intriguing one to pose in the context of a developing country. Pakistan’s growth record has been impressive over a relatively long period. The economy has grown at around six percent per annum in real terms since the early 60s. This growth pattern has bew achieved despite a number of adverse "shocks" during this period. There have been two wars, 1965 and 1971, the country was dismembered as a result of the second, and there have been a succession of violent political transitions. And in addition Pakistan has faced the adjustments enforced on many oil-importing developing countries as a result of the "oil shocks" of the 1970s. Further there has been a massive influx of refugees from the turmoil in Afghanistan, since the late 1970s. These are estimated to be around 3.5 million, or a quarter of the Afghan population. In this paper we examine the pattern of growth and public policy, in conjunction with some of the "exogenous shocks" described above, which have led to changes in the standards of living of different groups of the population. The basis of Pakistan’s sustained progress rests on the foundation of an innovative agricultural sector, supported by an extensive irrigation network. The latter dates in part to the last century, and is supplemented by substantial public investments since the 1950s. This pattern of public investment in infrastructure assisted in the rapid diffusion of high yielding varieties of cereals since the mid-60s, popularly known as the "Green Revolution". This process, it is held, spearheaded by the "middle-sized" farmers has led to substantial improvements in levels of income across a wide class of society [see e.g., Burki (1988)]. On the other hand it has been argued that the Green Revolution has both increased inequality, and led to immiserization of the poorest through increased landlessness. We examine some of the evidence in support these positions in this paper.